2003
DOI: 10.1128/aem.69.7.3911-3918.2003
|View full text |Cite
|
Sign up to set email alerts
|

Formation of 4-Hydroxy-2,5-Dimethyl-3[2H]-Furanone by Zygosaccharomyces rouxii : Identification of an Intermediate

Abstract: 13 C]FBP to the nutrient medium revealed that only exogenously supplied FBP was transformed to HDMF (6). It was assumed that at least one metabolic step takes place in the cell wall or membrane of the yeast. However, the biosynthesis in plants and microorganisms is still unclear since no enzyme or intermediate involved in HDMF formation has been identified so far. Recently, the chemical formation of HDMF from FBP in the presence of NAD(P)H was reported (11). The authors proposed the dicarbonyl compound 1-deoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
0
13
0
1
Order By: Relevance
“…The bioformation pathway of HDMF during fermentation is proposed by Z. rouxii from D-fructose-1,6-bisphosphate (Hara, Kusaka, Inagaki, Takahashi, & Wada, 2000). In addition, some previous studies showed that the formation of HDMF was significantly higher in soy sauce fermented by the combination of T. halophilus and Z. rouxii, compared to the single culture (Hauck, Brühlmann, & Schwab, 2003).…”
Section: Relative Peak Area Bmentioning
confidence: 99%
“…The bioformation pathway of HDMF during fermentation is proposed by Z. rouxii from D-fructose-1,6-bisphosphate (Hara, Kusaka, Inagaki, Takahashi, & Wada, 2000). In addition, some previous studies showed that the formation of HDMF was significantly higher in soy sauce fermented by the combination of T. halophilus and Z. rouxii, compared to the single culture (Hauck, Brühlmann, & Schwab, 2003).…”
Section: Relative Peak Area Bmentioning
confidence: 99%
“…2,5-dimethyl-4-hydroxy-3(2H)-furanone (DMHF), also known as furaneol, is an aroma compound found in strawberries, mangos, pineapples, raspberries, and various processed foodstuffs (Rodin et al, 1965;Ohloff, 1969;Larsen et al, 1992;Wein et al, 2002), and is extensively used as a food flavoring due to its low odor threshold and flavor-enhancing properties (Hauck et al, 2003). This compound is formed mainly as a result of the operation of the Maillard reactions between sugars and amino acids (Hayase et al, 1985;Blank and Fay, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Pada kecoa jantan , furanon digunakan sebagai sex pheromone. Furanon ini terdapat secara alami pada nanas dan strawberry dan membuat senyawa cita rasa pada keju dan wine (Martinelli et al, 2004;Hauck et al, 2003).…”
Section: Delisea Pulchraunclassified